Effects of Growing-Season Prescribed Burning on Vigor of the Noxious Weed Sericea Lespedeza (Lespedeza cuneata) in the Kansas Flint Hills - J. A. Alexander; W. H. Fick; J. Lemmon; C. A. Gurule; G. W. Preedy; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2016)
Sericea lespedeza (SL) was introduced into the United States from Asia in the late 19th century. Early land managers recognized that SL was adaptable; tolerant of shallow, acidic or low-fertility soils; and resistant to insects and disease. This combination of traits made SL a widely-used plant for reseeding strip-mined lands, highway right-ofways, dams, and waterways in the US for nearly a century. Regrettably, SL is highly fecund. Individual plants are capable of producing up to 850 lb of seed per acre annually. Vigorous seed production allows SL to rapidly infiltrate native grasslands that are adjacent to reseeding projects; seed can be transported great distances via the alimentary canal and hair of wild and domestic herbivores. In Kansas alone, SL has infested approximately 980 square miles of pasture, primarily in the Flint Hills region. The resulting damage to native habitats for wildlife and pasture quality for domestic herbivores has been devastating. The predominant grazing management practice in the Kansas Flint Hills involves annual spring burning in March or April, followed by intensive grazing with yearling beef cattle for a relatively short period from April to August. During seasonal grazing, 40 to 60% of annual graminoid production is removed and grazing lands then remain idle for the remainder of the year. Under this prevailing management practice, invasion by SL into the Tallgrass Prairie biome has steadily increased. Oklahoma State University researchers speculated that dormant-season, spring fires may stimulate SL growth by scarifying seeds lying on the surface of the soil. In contrast, plants with robust canopies respond more strongly to growing-season prescribed burns than to dormant-season prescribed burns. Previous research reported that application of growing season fire at 3-yr intervals decreased the rate of SL invasion. Therefore, the objective of our study was to evaluate the effects of growing-season prescribed burning of native tallgrass range on vigor of sericea lespedeza.
Keywords: sericea; cattle; burning